Pelatihan Peningkatan Kualitas Pembelajaran dengan Pemanfaatan Media Digital di SMK Muhammadiyah 15 Jakarta - Roslaini Roslaini; Martriwati Martriwati (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
In the era of School from Home (SFH) due to the outbreak of Covid-19 has certainly affected the learning process for all students. Students and teachers have to plunge into the new world in which they must adapt to the new pattern of education. Both of them, like it or not, should immerse in digital world, in the sense they have to acquire technology to run teaching learning process by virtual. For this reason, it is necessary for the team of Community Service (PkM) of Muhammadiyah University of Prof. Dr. Hamka to participate in supporting teachers’ teaching learning process at SMK Muhammadiyah 15 Jakarta to equip them with the knowledge of selecting the appropriate digital media for better teaching. The method used is giving training how to select digital media before implementing in the class. Therefore, this training started with a questionnaire, recognizing learning problems, selecting suitable digital media and putting them in a research proposal. The results of training show that the teachers are able to recognize learning problems, select the appropriate digital media, and put them in a research proposal. Through the post-questionnaire, the teachers realized the importance of selecting suitable digital media for virtual teaching in the time of online learning.